The Impact of Dabigatran and Rivaroxaban on Variation of Platelet Activation Biomarkers and DRT Following Percutaneous Left Atrial Appendage Closure - Li, Xiaoye; Zhang, Xiaochun; Jin, Qinchun; Li, Yanli; Zhou, Daxin; Lv, Qianzhou; Ge, Junbo (Frontiers in Pharmacology, 2021)
Background: The current post-procedure antithrombotic recommendation for left atrial appendage closure (LAAC) remains empiric. This study was designed to compare variations in platelet activation biomarkers and device related thrombosis (DRT) under different antithrombotic regimens following LAAC. Methods: This study enrolled 105 consecutive patients with atrial fibrillation who underwent LAAC successfully and received post-procedure anticoagulation with either dabigatran (N=33) or rivaroxaban (N=72). After 3 months of anticoagulation, thromboelastogram (TEG) was used to evaluate thrombin receptor activating peptide (TRAP)-induced platelet aggregation. Measurements of platelet activation biomarkers including TAT, P-selectin, vWF, and CD40L were performed immediately prior to the LAAC procedure and after 3 months of post-procedure anticoagulation. Repeated transesophageal echocardiography was performed to evaluate device related thrombosis (DRT) during follow-ups. Results: Three (4.2%) patients in the rivaroxaban and 4 (12.1%) patients in the dabigatran group experienced DRT events (OR=0.315, 95%CI: 0.066-1.489, P=0.129) during follow-ups. The TRAP induced platelet aggregation was statistically significantly higher in the dabigatran group (62.9% vs. 59.7%, P=0.028*). SStatistically significant increases in plasma concentration of TAT, P-selectin, and vWF were observed after 3 months of exposure to dabigatran as compared to rivaroxaban. An increased expression of platelet activation biomarkers was observed in DRT subjects compared to non-DRT subjects in terms of the P-selectin and vWF (65.28 ± 13.93 ng/L vs. 32.14 ± 12.11 ng/L, P=0.037; 501.92 ± 106.48 U/L vs. 280.98 ± 54.10 U/L, P=0.045; respectively). Multivariate regression analysis indicated that use of dabigatran might be an independent predictor of DRT (P=0.022; OR=4.366, 95%CI: 0.434-10.839). Furthermore, CHA2DS2-VASc score (OR=2.076, P=0.016) and CD40L (OR=1.015, P=0.021) were independent predictors of increased D-dimer levels. Conclusions: Post-LAAC anticoagulation with dabigatran may increase the risk of DRT by enhancing platelet reactivity. In light of this potential increased risk in DRT, we recommended against using dabigatran for post-procedural anticoagulation in patients who have undergone LAAC.